P82 | PROINFLAMMATORY BONE MARROW NICHES AND NEUTROPHIL ACTIVATION ARE ASSOCIATED WITH TIGIT EXPRESSION IN MULTIPLE MYELOMA (European Journal of Histochemistry)
Multiple myeloma (MM) is a hematological disorder due to the abnormal proliferation of clonal Plasma Cells (PCs) characterized by the increase of monoclonal immunoglobulins1. The interaction between MM cells and the bone marrow (BM) microenvironment is crucial to the progression and treatment of the disease. The PCs interaction with the hematopoietic cells induce the secretion of cytokines and growth factors, by establishing circuits that support PCs activation. In this context the malignant TIGIT positive PCs are able to interact with the T lymphocytes, a process that fuel the immune evasion, typical of the MM2. Our knowledge about the BM myeloma microenvironment is still poorly defined as well as the cellular interaction between PCs. We exploited BM biopsies of 22 MM patients. TIGIT was expressed in 86% (19/22) of evaluable samples. Among patients with PCs % >60% or FLC ratio >100, 92% were TIGIT+. Morphological differences were evident between groups: TIGIT-negative PCs were larger and altered, while TIGIT-positive PCs showed polarized nuclei and proximity to neutrophils. TIGIT-positive samples displayed increased neutrophils undergoing NETosis, as confirmed by neutrophil elastase and Ly6b co-expression (p=0.0067). Elevated IL-6 (p=0.0003) and IL-8 (p=0.004) in TIGIT-positive samples suggest a proinflammatory microenvironment promoting neutrophil recruitment and NETosis. In MM, the Neutrophil to lymphocyte ratio combines a marker of inflammation and the reduced cell turnover, reflecting alteration in the immune system. TIGIT expression in the bone marrow of MM patients is associated with more aggressive disease features and an inflammatory microenvironment enriched with NET-forming neutrophils. These findings support TIGIT as a potential biomarker of disease severity and a therapeutic target in MM.